Impacto de um programa de reabilitação pulmonar de 12 semanas na função cognitiva de portadores de doença pulmonar obstrutiva crônica - Viana, Cyntia Maria Sampaio (2010)
The reduction of cognitive function in patients with COPD is part of the comorbidities of the disease, reaching an incidence of up to 77%. The main areas of cognitive dysfunction appear in attention, memory, executive function and motor skills. Among the possible treatments to improve cognition in patients with COPD are the physical exercise programs, such as pulmonary rehabilitation, which have shown an important role in literature, even though with conflicting results. Objective: To evaluate the cognition improvement in patients with COPD after 12 weeks of pulmonary rehabilitation program and the influence of patient`s charactheristcs. The study is a clinical trial of time-series. Selected patients were those with COPD, aged between 40 and 75 years old, with GOLD stage II to IV, without severe comorbidities, literate and referred to the pulmonary rehabilitation program of Hospital de Messejana Carlos Alberto Studart Gomes from November 2008 to January 2010. The patients underwent neuropsychological tests to evaluate cognition with trained psychologist, before and after the pulmonary rehabilitation program that lasted three months. Control group of healthy patients with the same exclusion criteria of the COPD group, aged between 40 and 75 years old, literate, was used to compare the basal cognition between the groups. The COPD patients were stratified according to sociodemographic characteristics and tobacco intake in: Male group vs Female group; age <65 years old vs ≥ 65 years old; Educational level <8 years of study vs ≥ 8 years of study; Tobacco intake: <50 packs/years vs ≥ 50 packs/year. Continuous variables were described in the statistical analysis as means and standard deviations and relative frequencies for categorical. Mann-Whitney Test was used for independent samples and Wilcoxon for paired samples. Association between independent variables and changes in dependent variables scores (cognitive tests) was performed by random longitudinal linear regression test. P <0.05 statistically significant. Were included 34 patients, being 17 (50%) males and 17 (50%) female. The mean age was 65 ± 7. The severity by GOLD was: II (32.4%), III (44.1%) and IV (23.5%). As to the degree of education 29 (85.3%) was considered low grade (<12 years of study) and 5 (14.7%) high grade (> 12 years of study). Mean FEV1 was 0.96 ± 0.41. For the control group there were no significant differences in age or educational level in relation to COPD group. Regarding the basal cognitive tests, patients with COPD had worse performance on Verbal Fluency Test, Rey Auditory Verbal Learning Test and Trails Test part B. For the evaluation of cognition after pulmonary rehabilitation, there was statistically significant improvement in Rey Auditory Verbal Learning Test (RAVLT), which concerns the memory function; in the card 1 Stroop Test regarding to attention and mental flexibility and Trails Test part B which relates to executive function. Some independent variables were related to the variance of cognitive tests after pulmonary rehabilitation, as females had a worse performance in the Rey Auditory Verbal Learning Test compared to males; age had a negative influence on the Rey Auditory Verbal Learning Test; the educational level, the lower the worse score on the Stroop Test and the tobacco intake, the higher the worse performance on the FAS verbal fluency test. There was improvement in the cognitive function of patients with COPD after the 12-week pulmonary rehabilitation program, the socio-demographics factors influenced this improvement.